2021
DOI: 10.1093/socrel/srab002
|View full text |Cite
|
Sign up to set email alerts
|

Theorizing the Religious Habitus in the Context of Conversion to Islam among Polish Women of Catholic Background

Abstract: This article explores the conversion processes of Polish women of Catholic background to Islam. Data from participant observation of mosque-based, women-only weekend gatherings for converts and in-depth interviews with 29 Polish female converts to Islam are presented to illustrate the dialectic between the persistence and transformation of religious habitus. Our analysis demonstrates that in the conversion process, Catholic habitus remains pervasive, and shapes converts’ engagement with the new religion; howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…These responses also highlight that developing a disposition for solitary practice is more effortless for some than others; Ameerah's ambiguous attitude to individual practice in particular echoes the protracted process of developing a religious disposition by Mahmood's participants (2005) who had to shape their bodies and minds into appreciation of certain practices through repeated practice. Intentionally reforming one's disposition to solitary practice could be interpreted as creation of a new religious habitus (Krotofil et al 2021)-in this case, a "Covid habitus". However, the emphasis on "positive value of subjective religious signification" that centers individual experience (Versteeg and Roeland 2012, p. 123) is not all-pervasive in our dataset.…”
Section: Embracing the New Socially Distanced Everyday And Affirming Solitudementioning
confidence: 99%
“…These responses also highlight that developing a disposition for solitary practice is more effortless for some than others; Ameerah's ambiguous attitude to individual practice in particular echoes the protracted process of developing a religious disposition by Mahmood's participants (2005) who had to shape their bodies and minds into appreciation of certain practices through repeated practice. Intentionally reforming one's disposition to solitary practice could be interpreted as creation of a new religious habitus (Krotofil et al 2021)-in this case, a "Covid habitus". However, the emphasis on "positive value of subjective religious signification" that centers individual experience (Versteeg and Roeland 2012, p. 123) is not all-pervasive in our dataset.…”
Section: Embracing the New Socially Distanced Everyday And Affirming Solitudementioning
confidence: 99%
“…In other words, persistence and transformation can occur in the religious habitus' conversion process (Nur 2021). Previous studies have also shown that the process of cultural production across domains and cases is inseparable from the fields, the habitus, the agents' roles, and the available capital (Bok 2020;Jatmiko and Abdullah 2021;Krotofil et al 2021;Linda 2019;Reinhart 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Among the few, research in the United States (US) examines religious activities carried out by two religious organizations (Bok 2020), indicating a prospect of cooperation rooted in capital ownership. Another research reviews religion as a field of cultural production (Krotofil et al 2021), for example, how changes in religious practices resulting from conversion factors spur cultural production. The findings show that the old habitus is not completely lost but forms a dialectic with the new.…”
Section: Introductionmentioning
confidence: 99%
“…We discuss reasons for our respondents' conversion and how it affected their relationships with significant others in our other work:Krotofil et al (2021),Krotofil et al (forthcoming), and Abdallah-Krzepkowska et al (forthcoming).…”
mentioning
confidence: 94%